2022
DOI: 10.3390/nu14204426
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Investigations of (R)-3-Hydroxybutyrate Glycerides In Vitro and in Male and Female Rats

Abstract: TCN006, a formulation of (R)-3-Hydroxybutyrate glycerides, is a promising ingredient for enhancing ketone intake of humans. Ketones have been shown to have beneficial effects on human health. To be used by humans, TCN006 must be determined safe in appropriately designed safety studies. The results of a bacterial reverse mutation assay, an in vitro mammalian micronucleus study, and 14-and 90-day repeat dose toxicity studies in rats are reported herein. In the 14- and 90-day studies, male and female Wistar rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Although a statistical difference in CHOL levels was observed between the 15 and 30 mg/kg groups compared to the negative control group, it appears that the increase approaching the clinical range was attributable to the rise in HDL, or ‘good’ cholesterol. This suggests that LVM may exert some influence on the CHOL values in beagle dogs without toxicological significance [ 18 ]. Also, blood indicators combined with organ coefficient indexes, we found that continuous administration of LVM did not affect liver and kidney indexes and weights, and it did not produce accumulation effects and toxicological effects in the kidneys and liver of beagle dogs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a statistical difference in CHOL levels was observed between the 15 and 30 mg/kg groups compared to the negative control group, it appears that the increase approaching the clinical range was attributable to the rise in HDL, or ‘good’ cholesterol. This suggests that LVM may exert some influence on the CHOL values in beagle dogs without toxicological significance [ 18 ]. Also, blood indicators combined with organ coefficient indexes, we found that continuous administration of LVM did not affect liver and kidney indexes and weights, and it did not produce accumulation effects and toxicological effects in the kidneys and liver of beagle dogs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%